ANALISIS PENGARUH HARGA KOMODITAS MINYAK KELAPA SAWIT (CPO), TINGKAT INFLASI, NILAI TUKAR RUPIAH DAN VOLUME PENJUALAN KOMODITAS (CPO) TERHADAP HARGA SAHAM PADA PERUSAHAAN PENGHASIL KELAPA SAWIT (CPO) YANG TERDAFTAR DI BURSA EFEK INDONESIA - Johnnywinata '; Muchtar Mariso; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The objectives of this research is to analyze how the influence of the price of Crude Palm Oil (CPO), inflation rate, exchange rate and the level of sales volume of palm oil (CPO) to the stock price on plantations producing palm oil (CPO) which is listed on the Stock effect of Indonesia in 2008-2012, the results of this study are expected to contribute in addition to researchers, practitioners and also the investors in helping them to determine the decision whether to sell, buy or hold their shares with respect to changes in the price the stock of palm oil plantations caused by changes in the price of Crude Palm Oil (CPO), inflation rate, exchange rate and selling rate of palm oil. The data used is the publication of the Annual Report of each issuer and publication of the results of statistical IDX da also BI in 2008 until 2012. Sampling technique used was purposive sampling with certain criteria. Obtained a total sample of 11 Producing Oil Palm Plantation Company (CPO) which is listed on the Stock Exchange during the period of observation is 2008-2012 The analysis technique used is multiple regression equation least squares fitted with the classical assumption of normality, multicollinearity, and autocorrelation heterocedasticity to get the model linear estimation is not biased. The hypothesis was tested using t-statistics to test the significance of the partial regression coefficients at 95 % level of significance. From the test results, there are two independent variables that have an influence on the stock price on plantations producing palm oil (CPO) are: Price CPO and Sales Volume, while the other two independent variables, namely inflation and the exchange rate has no significant effect on the stock price on plantations producing palm oil (CPO) which is listed on the Indonesia Stock Exchange in the year 2008-2012.Keywords: Crude Palm Oil (CPO), inflation, exchange rate and sales volume.